The effects of exploration strategies and communication models on the performance of cooperative exploration - Tuna, Gurkan; Gulez, Kayhan; Gungor, V. Cagri (ELSEVIER, 2013)
Exploration with mobile robots is utilized in a wide range of applications including search and rescue missions, planetary exploration, homeland security; surveillance, and reconnaissance. Cooperative exploration offers the potential of exploring an unknown zone more quickly and robustly than single-robot case. However, coordinating multiple robots is a challenging task due to heterogeneous processing and communication requirements, and the complexities of exploration algorithms. This paper presents a comparison of different cooperative exploration strategies, such as frontier-based exploration, market-driven exploration, and role-based exploration, based on their exploration performances and processing time requirements. To show the effect of CPU power on the processing time of the exploration algorithms, two notebooks and a netbook with different specifications have been extensively used. Comparative simulation results of our own application developed in Java show that the processing time requirements are consistent with the computational complexities of the exploration strategies. The results we obtained are consistent with the CPU power tests of independent organizations, and show that higher processing power reduces processing time accordingly. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Cooperative exploration strategies; Communication models; Processing time requirements; Exploration performances; NetBeans IDE; MULTIROBOT EXPLORATION; Computer Science; Telecommunications